A differentiated multi-loops bath recirculation system for precision machine tools. (5th February 2015) - Liu, Teng; Gao, Weiguo; Tian, Yanling; Zhang, Hongjie; Chang, Wenfen; Mao, Ken; Zhang, Dawei
Abstract: Traditional bath recirculation cooler for precision machine tools always has the uniform and open-loop cooling strategy onto different heat generating parts. This causes redundant generated heat being transferred into the machine structure, and results in unsatisfactory thermal errors of precision machine tools. For the solution of this problem, this paper presents the differentiated multi-loops bath recirculation system. The developed system can accomplish differentiated and close-loop cooling strategies onto machine heat generating parts during its operation. Specially, in order to illustrate the advantages of this system, constant supply cooling powers strategy is presented with its applications onto a certain type of built-in motorized spindle. Consequently, advantages of the proposed strategy based on the differentiated multi-loops bath recirculation system are verified experimentally in the environment within consistent temperature ( T R = 20 ± 0.3°C). Compared with room temperature tracing strategy based on the traditional bath recirculation cooler, the constant supply cooling powers strategy is verified to be advantageous in spindle temperature stabilization and thermal errors decrease. Highlights: Structure and principle of differentiated multi-loops bath recirculation system. Principle of machine differentiated temperature control of this system. Advantage of constant supply cooling powers strategy based on this system.